2006
DOI: 10.1038/sj.bjp.0706865
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of axonal maturation and prevention of memory loss in mice by extracts of Astragalus mongholicus

Abstract: Background and purpose: Neurons with atrophic neurites may remain alive and therefore may have the potential to regenerate even when neuronal death has occurred in some parts of the brain. This study aimed to explore effects of drugs that can facilitate the regeneration of neurites and the reconstruction of synapses even in severely damaged neurons. Experimental approach: We investigated the effects of extracts of Astragalus mongholicus on the cognitive defect in mice caused by injection with the amyloid pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
74
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 23 publications
2
74
0
Order By: Relevance
“…1A. AS-IV has comprehensive pharmacological functions, including anti-inflammatory and antioxidative activity, and is able to reduce infarct size and improve post-ischemic brain function (20)(21)(22). However, few studies have investigated whether AS-IV prevents mitochondrial dysfunction via MsrA.…”
Section: Introductionmentioning
confidence: 99%
“…1A. AS-IV has comprehensive pharmacological functions, including anti-inflammatory and antioxidative activity, and is able to reduce infarct size and improve post-ischemic brain function (20)(21)(22). However, few studies have investigated whether AS-IV prevents mitochondrial dysfunction via MsrA.…”
Section: Introductionmentioning
confidence: 99%
“…Astramembranoside 6 Hz, H-1Љ) were observed, indicative of the presence of two b-linked sugar units. The sugar was identified as glucose by acid hydrolysis and TLC comparison with an authentic sample.…”
mentioning
confidence: 99%
“…(Leguminosae) has long been one of the most important tonic herbs used in traditional Chinese medicine. Studies of its pharmacology and clinical use have demonstrated that Astragali Radix has many biological functions, including hepatoprotection, 3,4) neuroprotection against ischemic brain injury, 5,6) immunologic properties, 7-9) cardiotonic 10,11) and antiaging activities, 12) gastroprotection, 13) adjuvant 14) and antitumor effects, 15,16) antiinflammatory effects, 17,18) and stimulation of the growth of new tissues. 19,20) The major bioactive components of A. membranaceus are triterpene saponins and isoflavonoids.…”
mentioning
confidence: 99%
“…(Leguminosae), has been used as one of the most important tonic herbs in traditional medicine. Pharmacological studies of AR have demonstrated that AR possesses many biological functions, including hepatoprotective (Ríos et al, 1997;Gui et al, 2006), neuroprotective effect against ischemic brain injury (Luo et al, 2004;Tohda et al, 2006), immunological properties (Shao et al, 2004;Li et al, 2007;Cho et al, 2007a), cardiotonic (Zhang et al, 2006a;Zhang et al, 2006b), antiaging activities (Lei et al, 2003), gastroprotective (Navarrete et al, 2005), adjuvant (Rajput et al, 2007), antitumor effects (Cho et al, 2007b;Tin et al, 2007), anti-inflammatory (Zhang et al, 2003), and the growth of new tissues (Cheng et al, 2006;Choi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%